3+2ab-4ac+6bc=

Simple and best practice solution for 3+2ab-4ac+6bc= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+2ab-4ac+6bc= equation:


Simplifying
3 + 2ab + -4ac + 6bc = 0

Solving
3 + 2ab + -4ac + 6bc = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + 2ab + -4ac + -3 + 6bc = 0 + -3

Reorder the terms:
3 + -3 + 2ab + -4ac + 6bc = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 2ab + -4ac + 6bc = 0 + -3
2ab + -4ac + 6bc = 0 + -3

Combine like terms: 0 + -3 = -3
2ab + -4ac + 6bc = -3

Add '-6bc' to each side of the equation.
2ab + -4ac + 6bc + -6bc = -3 + -6bc

Combine like terms: 6bc + -6bc = 0
2ab + -4ac + 0 = -3 + -6bc
2ab + -4ac = -3 + -6bc

Reorder the terms:
3 + 2ab + -4ac + 6bc = -3 + -6bc + 3 + 6bc

Reorder the terms:
3 + 2ab + -4ac + 6bc = -3 + 3 + -6bc + 6bc

Combine like terms: -3 + 3 = 0
3 + 2ab + -4ac + 6bc = 0 + -6bc + 6bc
3 + 2ab + -4ac + 6bc = -6bc + 6bc

Combine like terms: -6bc + 6bc = 0
3 + 2ab + -4ac + 6bc = 0

The solution to this equation could not be determined.

See similar equations:

| 2(x-2)+2x=4 | | (X-19)+17=63 | | -24b=-48 | | 1p^2+2p-24=0 | | 7(b+10)= | | -2/3n-4=5 | | (x+16)(x-18)=180 | | 4x+10=3x-4 | | -2(u+1)=-2(9u-7)+4u | | 3(-2+7x)=-27 | | 1250w^10z^5/20w^2z^2 | | 2z+7=3z-11 | | 1-5x=6x-10 | | 3(u+2)+2u=7(u-1)+1 | | 3x+2(3x+5)-4(3x+4)+3(3x+2)+8=0 | | (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x | | -3.2b+6=-5.1 | | 4(3x-1)=45 | | 2x^2+7=8x | | -5-2x+x=3 | | -2500-4.05=3000 | | -5(x+12)-13-=-24 | | 4.3b+5=8.1 | | 8.5x^3=79.687x+165.9891 | | 2x^2+7x-2=-2x^2+2x |

Equations solver categories